Carotid sinus hypersensitivity, as a cause of syncope, in a patient with coronary artery disease: A case report. (June 2022) - Dhakal, Bishal; Simkhada, Nabin; Pathak, Bishnu Deep; Subedi, Binaya; Thapa, Dilip; Acharya, Suchita; Prabhat, K.C.; Karki, Parag
Abstract: Introduction: Carotid sinus hypersensitivity is one of the unexplained causes of syncope in old age. There are variations in presentations of carotid sinus hypersensitivity. Case presentation: A 56-year-old male, known case of coronary artery disease, presenting with syncope, was diagnosed as carotid sinus hypersensitivity finally. He was treated with the placement of dual chamber pacemaker. Clinical discussion: The etiology of unexplained syncope is itself a challenging for clinicians. In the presence of a known risk factor, it is uncommon for carotid sinus hypersensitivity to be present as a cause of syncope. Conclusions: Hence, the rare disorder like carotid sinus hypersensitivity should also be considered as a cause of syncope despite the presence of co-morbidity like coronary artery disease. Highlights: Carotid Sinus Hypersensitivity is one of the causes of unexplained syncope in old age. Coronary artery disease is one of the etiological factors in unexplained syncope. Carotid Sinus Hypersensitivity is an uncommon cause of syncope in presence of coronary artery disease. The variations in carotid sinus hypersensitivity should be differentiated and treated accordingly.